A Review of Plant Practice at Molycorp Inc., Questa Division - A. Filyk; R. Woods (Society for Mining, Metallurgy & Exploration, 1976)
The current plant practice at Molycorp, Inc., Questa Division, a molybdenum producer in northern New Mexico, is described. An outline of crushing, grinding, flotation, drying, and tailings disposal is included, with emphasis on metallurgy.